Long-range angular correlations on the near and away side in p-Pb collisions at √sNN=5.02 TeV - Abelev, Betty; Angelov, Venelin; Busch, Oliver; Fasel, Markus; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Klein, Jochen; Krawutschke, Tobias; Kweon, MinJung; Lohner, Daniel; Lu, Xianguo; et al. (Physics letters, 2013)
Angular correlations between charged trigger and associated particles are measured by the ALICE detector in p-Pb collisions at a nucleon-nucleon centre-of-mass energy of 5.02 TeV for transverse momentum ranges within 0.5<pT,assoc<pT,trig<4 GeV/c. The correlations are measured over two units of pseudorapidity and full azimuthal angle in different intervals of event multiplicity, and expressed as associated yield per trigger particle. Two long-range ridge-like structures, one on the near side and one on the away side, are observed when the per-trigger yield obtained in low-multiplicity events is subtracted from the one in high-multiplicity events. The excess on the near-side is qualitatively similar to that recently reported by the CMS Collaboration, while the excess on the away-side is reported for the first time. The two-ridge structure projected onto azimuthal angle is quantified with the second and third Fourier coefficients as well as by near-side and away-side yields and widths. The yields on the near side and on the away side are equal within the uncertainties for all studied event multiplicity and pT bins, and the widths show no significant evolution with event multiplicity or pT. These findings suggest that the near-side ridge is accompanied by an essentially identical away-side ridge.
Im Titel steht "sNN" unter dem Wurzelsymbol
Im Titel ist "NN" in sNN tiefgestellt
ALICE Collaboration: Betty Abelev, Venelin Anguelov, Oliver Busch, Markus Fasel, Peter Glassel, Robert Grajcarek, Norbert Herrmann, Jochen Klein, Tobias Krawutschke, Jung Kweon, Daniel Lohner, Xianguo Lu, Antonin Maire, Jae Mercado Perez, Ken Oyama, Chiara Pachmayer, Johannes Reygers, Martin Schicker, Johanna Stachel, Hendrik Stiller, Jochen Ulrich, Sara Vallero, Yifei Wang, Stefan Windelband, Alice Zimmermann und weitere 950
Gesehen am 30.04.2021